2008
DOI: 10.1136/jme.2007.023713
|View full text |Cite
|
Sign up to set email alerts
|

Do faculty and resident physicians discuss their medical errors?

Abstract: Most generalist physicians in teaching hospitals report that they usually discuss their errors with colleagues, and more than half have tried to role-model discussions. However, a significant number of these physicians report that they do not usually discuss their errors and some do not know colleagues who would be supportive listeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 38 publications
(44 reference statements)
3
33
0
1
Order By: Relevance
“…Clinicians who discuss the clinical error with colleagues do this usually for professional and personal reasons including the need for emotional support (Kaldjian et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians who discuss the clinical error with colleagues do this usually for professional and personal reasons including the need for emotional support (Kaldjian et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Much work has been done studying the effect of incidents on patients, 5,6 but examining the effect on caregivers, also referred to as "the second victim," [2][3][4] is in its infancy. Previous studies have focused on the acute care system and medical residents [7][8][9][10][11][12][13][14][15][16] or a compilation of acute and primary care. [17][18][19][20] Only 2 studies have explored the emotional impact of incidents on primary care providers alone.…”
mentioning
confidence: 99%
“…Similar to a medical study [39], the PTs argued in favour of the discussion of errors with colleagues, especially targeted at collegial support. In medicine, studies found that this approach enables peer learning by seeing each other as role models [39]. A similar range of considerations was found in our study.…”
Section: Discussionmentioning
confidence: 93%
“…The frequent reference to a character of integrity may reflect the significance of virtue ethics [39-41] for individual orientation as a psychotherapist. It suggests that human qualities play an important role for the profession and personal virtues of (famous) psychotherapists might offer a general ethical orientation.…”
Section: Discussionmentioning
confidence: 99%